Behavioral effects of Hypericum uniglandulosum essential oil inhalation on rat model of Alzheimer’s disease - Akbaba, Emel; Bağcı, Eyüp (My University, 2017)
Hypericum (Hypericaceae) species have been attracting interest due to their sedative and relaxing actions. In the current study, rats exposed to Hypericum uniglandulosum essential oil (HYP) at the concentrations of 1.0%; and 3.0%, by inhalation during 15 minutes for 21 continuous days in plexyglass boxes were evaluated on scopolamine model of Alzheimer’s disease. Memory-enhancing effects of HYP were tested by well-characterized tasks namely Y-maze test and radial-arm maze test. Furthermore, anxiolytic, and antidepressant effects of the inhaled essential oil were evaluated by elevated plus maze and forced-swimming tests, respectively. As expected, scopolamine administration decreased the spontaneous alternation percentage in Y-maze test, and working memory errors and reference memory errors in radial-arm maze test. HYP 1% and HYP 3% administration in scopolamine-induced rats caused statistically significant increases on the spontaneous alternation percentage in Y-maze task. Number of arm entries do not show any significant differences between scopolamine-alone treated and Sco+ HYP1% and Sco+HYP3% treated rats; thus, essential oil treatment does not change the motor activity in rats. In order to evaluate spatial memory performances further, radial-arm maze test was used. Scopolamine treatment showed an increase on the working memory errors, a type of short-term memory, and reference memory errors, a type of long- term memory, in this test. However, HYP inhalation significantly decreased these values. These results show the spatial memory-enhancing activities of the inhaled HYP in scopolamine-treated rats. In addition, anxiolytic and antidepressant-like effects of inhaled HYP were assessed. Diazepam, an anxiolytic drug, significantly increased the time spent in the open arms, number of open arm entries and number of crossings in the elevated plus maze task as compared to control rats. However, scopolamine-alone treated rats showed decreases in these parameters. HYP 1% and HYP3% inhalation increased these values in scopolamine –induced rats, therefore, acted as an anxiolytic drug. Forcedswimming test was used to evaluate antidepressant-like behavior of rats. As expected, tramadol, known antidepressant agent, increased the swimming time, and decreased the immobility time as compared to control group. Scopolamine-alone treated rats exhibited significant decrease in the swimming time, while increasing the immobility time. Both doses of HYP, but especially HYP1% significantly decreased the immobility time and increased the swimming time as compared to scopolamine-alone treated rats. In conclusion, Hypericum uniglandulosum essential oil inhalation was showed to induce memory-enhancing, anxiolytic and antidepressant-like effects on scopolamineinduced rats. These results suggest that Hypericum uniglandulosum essential oil could be used as an alternative or complementary therapy against neurological diseases related to Alzheimer’s Disease.
Bildiri - Yayımlanmış
Keywords: Hypericum uniglandulosum essential oil; Scopolamine; Memory; Anxiety; Depression